Political Communication Model in Egy Sunardi Nurdin's Winning in the Village Head Election - Andi Astinah Adnan; Muhammad Rais Rahmat Razak; Adam Latif; Muh. Rusdi; Hariyanto Hariyanto (Faculty of Law, Universitas Pekalongan, 2022)
The High community participation in participating in village head elections indicates intense competition between candidates, so a strategy is needed to build communication with the community, especially by holding village head elections simultaneously and including candidates with a background of former contextual candidates. The purpose of this research is to find out the political communication model in winning Egy Sunardi Nurdin in the 2021 election for the Head of Compong Village, Pitu Riase District, Sidenreng Rappang Regency. The research method used is a descriptive qualitative method. By using purposive sampling technique. Observations, interviews. Research documents were collected and processed using the Nvivo 12 Plus data analysis technique. The results of the study show that the political communication model used by Egy Sunardi Nurdin when communicating with the public uses political communication as measured by indicators; political communicators, political messages, channels or media, goals or targets and influence or effects of political communication. All indicators have been implemented properly. In contrast to the previous context, the most dominant indicator used in the 2021 village head election is